Advanced Cardiac Life Support Compliance and Outcomes in In-Hospital Cardiac Arrests: A Prospective Observational Study - Jayasree, Kurupatha Menatha; M, Mounika; S, Shilpa; S, Sandhya; S, Swetha (Indian Journal of Pharmacy Practice)
Background: Advanced Cardiac Life Support (ACLS) guidelines are designed to improve outcomes following cardiac arrest. However, real-world compliance varies, potentially affecting survival rates. Materials and Methods: This prospective cross-sectional study analyzed 85 In-Hospital Cardiac Arrest (IHCA) cases over six months at the Department of Emergency Medicine, SVIMS, Tirupati. ACLS protocol adherence was assessed using a standardized checklist covering airway management, ventilation, CPR quality, defibrillation, medication administration, and documentation. The primary outcome was Return of Spontaneous Circulation (ROSC); secondary outcomes included survival to admission/discharge and neurological status (Cerebral Performance Category, CPC). Data were analysed using chi-square tests and descriptive statistics (SPSS v27). Results: ROSC was achieved in 57 of 85 cases (67.1%). Early CPR initiation and ROSC within 10 min were significantly associated with better outcomes (p<0.001). High-quality chest compression rates (100-120/min) were maintained in 32.9% (28/85), and adequate depth (5-6 cm) in 64.7% (55/85). Among patients with shockable rhythms (58/85), only 4 (6.9%) received defibrillation within the recommended 2-min window. Epinephrine was administered appropriately in all cases. Documentation quality was high, with 90.6% (77/85) of events fully recorded. Conclusion: Improved compliance with ACLS protocols-especially timely CPR, early defibrillation for shockable rhythms, and proper medication timing-is strongly associated with higher ROSC rates in in-hospital cardiac arrest. Identified gaps, particularly in defibrillation timing and CPR quality, highlight the need for targeted training, regular audits, and strict protocol adherence.
Keywords: ACLS; In-Hospital Cardiac Arrest; ROSC; CPR Quality; Defibrillation; Protocol Compliance